Framing Analysis of Increasing Fuel Prices News on cnnindonesia.com - Abidin, Kurniati; Rosniar, Rosniar; Aryadi, Rahmat; Wandi, Wandi (State Islamic Institute of Bone, Indonesia, 2024)
This research discusses the framing of issues carried out by the online media cnnindonesia.com in reporting on the increase in fuel prices officially announced by President Joko Widodo. The aim of this research is to analyze the issue framing strategy used by cnnindonesia.com in packaging news about fuel price increases. This type of research is qualitative research using media text analysis techniques in the form of Robert N. Entman's framing model analysis of 18 news stories released by cnnindonesia.com on Saturday 3 September 2022. The results of the research show that the issue framing strategy used by cnnindonesia.com is in its reporting. provides a definition of the problem as a global economic problem and has an impact on social problems. An increase in the APBN is the cause of problems and places the government as an actor or source of problems. The moral decision was framed from the president's statement that it was difficult to make a decision regarding the increase in fuel prices and constructed the repressive actions of members of the National Police against demonstrators. Presenting a solution to the problem by framing a political narrative battle between the government and the opposition and explaining that the National Police Chief must be responsible for the repressive actions carried out by the police against students and workers in the action against the increase in fuel prices in all regions.